AMBIGUOUS PROCESSES IN HIGHER EDUCATION PEDAGOGY - Alevtina S. Robotova (Moscow Polytechnic University, 2016)
The paper dwells on the discrepant events that take place in higher school pedagogy. Above all, the matter concerns the implementation of a competence approach, its risks, limitations, unsolved and unsolvable problems. The other point at issue is a technological approach that induces the teacher to be more organized and to focus on structure, dynamics of learning, concentration on subject, time economy. The author casts doubts on the expediency of standardization of teacher's and student's activities. One more aspect of the problem relatesto pedagogical texts and publications with ambiguous interpretation and variant reading ofterms and notions. These tendencies do not contribute to communication and cooperation between researchers and teachers, between theory and educational practice.